2020
DOI: 10.3390/ani10030520
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production of Lacaune Sheep with Different Degrees of Crossing with Manchega Sheep in a Commercial Flock in Spain

Abstract: The objective of the present study was to evaluate the effect of the grade of crossbreeding (Lacaune x Manchega) and environmental factors on milk production in a commercial flock in Spain. A total of 5769 milk production records of sheep with different degrees of purity of the Lacaune breed crossed with Manchega were used as follows: 100% Lacaune (n = 2960), 7/8 Lacaune (n = 502), 13/16 Lacaune (n = 306), 3/4 (n = 1288), 5/8 Lacaune (n = 441) and 1/2 Lacaune: Manchega (n = 272). Additional available informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
3
8
1
Order By: Relevance
“…The average DMY in our study was similar to those reported in the same breed (Fernandez et al 1995), and in the Comisana (Sebi et al 2000), and Chios breeds (Ploumi et al 1998), but was higher than were those reported in the Manchega and East Friesian breeds (Angeles-Hernandez et al 2017) and crossed ewes (Mioč et al 2009;Robles Jimenez et al 2020;Angeles-Hernandez et al 2018). Milk yields in Churra ewes were lower than were those in specialized dairy breeds such as Awassi, Lacaune, and Assaf (Elvira et al 2013;Gootwine and Goot 1994;Gootwine and Pollot 2000), and the differences are mainly because of genetic factors.…”
Section: Discussionsupporting
confidence: 88%
“…The average DMY in our study was similar to those reported in the same breed (Fernandez et al 1995), and in the Comisana (Sebi et al 2000), and Chios breeds (Ploumi et al 1998), but was higher than were those reported in the Manchega and East Friesian breeds (Angeles-Hernandez et al 2017) and crossed ewes (Mioč et al 2009;Robles Jimenez et al 2020;Angeles-Hernandez et al 2018). Milk yields in Churra ewes were lower than were those in specialized dairy breeds such as Awassi, Lacaune, and Assaf (Elvira et al 2013;Gootwine and Goot 1994;Gootwine and Pollot 2000), and the differences are mainly because of genetic factors.…”
Section: Discussionsupporting
confidence: 88%
“…The parity had a great effect on milk production of the ewes; animals in the first or fifth parity had lower TMY, SMY and DMY than ewes in the second or third parities. This was in concordance with the findings of Robles Jimenez et al (2020), who reported the highest milk yield in the second, third and fourth parities. The litter size had no significant effect on the milk production traits, which is in line with the results published by Oravcová et al (2006).…”
Section: Discussionsupporting
confidence: 93%
“…The litter size had no significant effect on the milk production traits, which is in line with the results published by Oravcová et al (2006). However, Robles Jimenez et al (2020) found a signifi-cant effect of litter size on TMY of ewes. Finally, temperament had a significant effect on TMY, SMY and DMY of ewes.…”
Section: Discussionsupporting
confidence: 89%
“…East Friesian and Lacaune are the two most common dairy breeds worldwide [ 97 , 98 ], both being wool breeds, with the East Friesian being slightly more heat resistant, based on THI values ( Table 4 ). According to Figure 3 , the central region of the Agreste mesoregion (including the microregions of Garanhuns, Brejo, and the southern part of Ipojuca), as well as a small part of the extreme west of it (northwest of the microregion of Vale do Ipanema), may be well suited to both of these breeds.…”
Section: Resultsmentioning
confidence: 99%